PENERAPAN PERMAINAN LACAK KATA DENGAN PENDEKATAN BERMAIN KREATIF UNTUK MENINGKATKAN PEMEROLEHAN BAHASA PADA ANAK USIA DINI - Santi dan M.Jakfar IS, Yulia (Jurnal Pendidikan Dasar (JUPENDAS))
The ability to speak is one aspect that was developed in early childhood. Language plays an important role as a communication tool to develop other aspects. This research was conducted in kindergarten Lhokseumawe city. This study aims to determine the application of the word chain game with the media card in language acquisition. Studied language acquisition is the acquisition through the game because in the game led to the language. Competition with the media card is very popular word picture of children. Therefore, in order that the child as much as possible to get of language used race technique with a variety of motion. Walk, run, jump, and even crawl used of games implementation strategy. This is done in addition to motivating children can also be used as a means so that children do not feel bored or fed in carrying out activities with regard to language acquisition . The results obtained in the experimental group with pre-test scores of 68, 41 while the results of the posttest score of 81.86 which can mean a significant increas. A recommendation is intended primarily for teachers and educational institutions in order to facilitate activities that refers to the creativity of teachers in order to make innovation in learning is mainly associated with language acquisition . Keywords: Track Word Games , Media Card , Language Acquisition Early childhood